Changes in phagocytic function with glycaemic control in diabetic patients. - MacRury, S M (1989)
Phagocytic function was assessed by serial whole blood chemiluminescence in poorly controlled type 2 (non-insulin dependent) diabetic patients during efforts to improve glycaemic control and compared with a group of well controlled type 1 (insulin dependent) diabetic patients. Chemiluminescence (corrected to a standard polymorphonuclear count) remained below normal (0.15-0.30 photons/second/cell) for most of the type 2 patients until 12 weeks when the value was significantly increased in patients showing improved glycaemic control (mean (range) 0.25 (0.01-0.43) photons/second/cell) compared with those showing no improvement (0.12(0.01-0.31) photons/second/cell). There was a significant inverse correlation of delta HbA1 with delta chemiluminescence. Although mean chemiluminescence for the type 1 diabetic patients was within the normal range, there was a wide scatter of values (0.19 (0.04-0.43) photons/second/cell) and there was no significant difference compared with the final value of type 2 patients with improved control. Glycaemic control is therefore a major determinant of phagocytic function in diabetic patients, but other factors must contribute, particularly in type 1 (insulin dependent) patients.